SOCIOLINGUISTICS DYNAMICS OF TRANSGENDER IDENTITY FORMATION: AN INQUIRY INTO LINGUISTIC FEATURES - Ali Raza; Dr. Aftab Akram (International Journal of Contemporary Issues in Social Sciences, 2024)
This research addresses the everlasting linguistic issue that concerns the sociolinguistic dynamics of transgender identity construction in Pakistan, with a specific focus on the role of Hijra Farsi vocabulary. Drawing on language and identity theory and intersectionality theory, the study analyses how language creates transgender identity within the Pakistani context, examining intersecting identities such as gender, sexuality, religion, and socioeconomic class. In this qualitative research, the complexities of Hijra Farsi vocabulary and its implications for transgender identity have been analyzed from the sociolinguistics perspective. The findings of this case study demonstrate the enormous impact of Hijra Farsi on the construction and expression of transgender identity, underlining its role in defining social structures, roles, and communal positions. The study underlines the necessity of linguistic recognition, social acceptance, and empowerment for transgender individuals in Pakistani society. By integrating theoretical frameworks and undertaking a thorough investigation of language usage and social situations, this research contributes to a greater understanding of the sociocultural dynamics shaping transgender experiences in Pakistan. Ultimately, this study serves as a call to action for politicians, scholars, and society to realize the function of language in developing transgender identities and to strive towards constructing more accepting and supportive settings for transgender individuals.